Weed management in cassava (Manihot esculenta Crantz) with selected pre- and post-emergence herbicides under alternative application sequence - Alabi, M.A. (University of Ibadan, 2022)
Cassava is a major crop in Africa, but weed management at its early growth stage is a problem. Pre-emergence Herbicides (PrH), often supplemented with Post-emergence Herbicides (PoH), are used for Weed Management (WM) in cassava. Delayed application of PrH could necessitate the use of PoH before PrH. There is a dearth of information on the effects of application of PoH before PrH as a WM strategy in cassava. Therefore, this study was conducted to evaluate some PrH and PoH and their alternative application sequences on WM, growth and yield of cassava. Three PrH: sulfentrazone, flumiosaxin+pyroxasulfone and indaziflam+isoxaflutole at 0.6, 0.11+0.14 and 0.068+0.20 kg a.i./ha, respectively and three PoH: clethodim+lactofen (0.21+0.41 kg a.i./ha), trifloysulfuron-sodium (5.25 g a.i./ha) and carfentrazone-ethyl (5.84 g a.i./ha) were evaluated in cassava (TMEB419) plots planted at 1x0.8 m2. The PrH were evaluated in plots laid in a Randomised Complete Block Design (RCBD). Plots treated with atrazine+S-metolachlor (0.73+1.30 kg a.i./ha) plus 2-Hoe-Weeding (ASm+2HW), weed-free and a weedy-check served as controls. Cassava Plant Height (CPH)-cm, stand count and Weed Dry Weight (WDW)-g/m2 per plot were measured at eight Weeks After Planting (WAP). In another experiment, two spray methods (banded and broadcast) of the PoH at two WAP were evaluated on sprouted cassava in a split-plot design. Spray methods and PoH were the main and sub-plots, respectively. Crop injury (%) and Weed Control Efficacy (WCE)-% were assessed. Thereafter, two sequences of application of PrH and PoH (PrH-PoH and PoH-PrH) were evaluated using split-plot arrangements in RCBD. The PrH or banded PoH were either the main or sub-plots in the sequences. Data were collected on WCE and cassava Storage Root Yield-SRY (t/ha). All experiments were replicated three times. Data were analyzed using descriptive statistics and ANOVA at α0.05. The CPH ranged from 38.0±1.2 (sulfentrazone) to 53.2±1.3 (weed-free). Stand count ranged from 10471.3±0.0 (indaziflam+isoxaflutole) to 11976.1±0.0 (weed-free). Significant reduction (%) in WDW relative to the maximum from weedy-check (110 g/m2) was in the order: 76.4 (sulfentrazone) <82.1 (flumioxazin+pyroxasulfone) <87.3 (indaziflam+isoxaflutole) <89.1 (ASm+2HW) <91.8 (weed-free). Broadcast spray caused 55.19 ±10.7% crop injury which was significantly higher than 7.4 ±7.0% in banding. Crop injury of 92.2±10.7% (carfentrazone-ethyl), 54.8±10.7% (trifloysulfuron-sodium) and 19.0±7.1% (clethodim+lactofen) due to broadcast-spraying were significantly higher than 6.3±7.0%, 7.8±7.0% and 8.2±7.0%, respectively in band-spraying. The WCE at 79.0±0.6% (carfentrazone-ethyl) was significantly lower than 88.4±0.6% (trifloysulfuron-sodium) and 97.0±0.6% (clethodim+lactofen). The WCE in PrH-PoH was significantly higher than in PoH-PrH. The WCE involving PrH-PoH application was 38.0% (sulfentrazone), 29.4% (flumioxazin+pyroxasulfone), 28.1% (carfentrazone-ethyl) and 22.3% (trifloysulfuron-sodium) significantly higher than those of their PoH-PrH. However, those of indaziflam+isoxaflutole (7.0%) and clethodim+lactofen (6.3%) were not significantly different. The SRY of 14.0±1.9 (sulfentrazone) was significantly lower than 28.7±1.9 (flumioxazin+pyroxasulfone) and 31.5±2.0 (indaziflam+isoxaflutole) across the PoH, while 22.7±1.9 (carfentrazone-ethyl), 23.9±1.9 (trifloysulfuron-sodium) and 26.7±1.9 (clethodim+lactofen) across the PrH were comparable. Indaziflam+isoxaflutole and flumiosaxin+pyroxasulfone, and banded spray of trifloysulfuron-sodium and clethodim+lactofen enhanced cassava growth and weed control efficacy. Sequences involving clethodim+lactofen before or after indaziflam+isoxaflutole improved weed control efficacy and yield of cassava.